Efek Imunostimulan Ekstrak Etanolik Herba Pegagan (Centella asiatica (L.) Urban) terhadap IgG Mencit Jantan - Shirly Kumala; Aulia Tisna Dewi; Yun Astuti Nugroho (Fakultas Farmasi Universitas Pancasila, 2004)
The immunostimulating effect of an ethanolic extract of Pegagan herbs to male mice has been determined. Thirty male mice divided into five groups (P1-P5) were induced by 1% sheep red cells for 14 days. P1, P2 and P3 were treated with three doses of an ethanolic extract 4.124 mg/20g BW, 8.25 mg/20g BW and 16.5mg/20gBW respectively. P4 was a positive control using Stimuno 0.55 mg/20g BW, and P5 was a negative control using distilled water Blood samples were taken at day 1, 8 and 15, and the concentration of IgG was measured by Radial Immunodiffusion method. A two way Anova showed no significant difference between P1, P2, and P5, but P3 was higher than P4. The obtained results showed that the ethanolic extract of 16,5 mg has a potent immunostimulating effect.